Revealing Character Personality Traits In Short Films - Chua, Daniel (Universiti Malaysia Sarawak (UNIMAS), 2016)
The thesis focuses on the research of personality traits in characters portrayed in short films. The characters and their very own vibrant personalities are the backbone of each story thus their personalities play a huge role in shaping the plot of the story. The problem statement given is the limitation in terms of function (form) in short films, limits the tools given to shape character personality traits. Duration in short films are a limiting factor when creating in depth characters compared to feature length films. The objective of this research is to research about the techniques readily available to reveal personality traits of characters in short films. Thus several data collection techniques are used in this thesis in forms of interviews, script analysis, literature analysis and film analysis in terms of structure and character development. The interviewees are Mr. Hassan Abd. Muthalib and Mr. Bernard Chauly respectively. The type of analysis used is from qualitative methods and carried out using case study and content analysis. For the findings of this research, a diagram using the data available has been constructed using the act structure to display the end results of this research. The findings reveal the two key elements (turning points, core morality values) which are the main essentials to creating in depth characters within a short duration of time.